The Ritual of the Rise of the Dango as a Reflection of the Dayak Ethnic Tradition (Study of Cultural and Religious Educational Value) - Herlina, Herlina; Hastiani, Hastiani; Hariadi, Try (Greenation International Journal of Law and Social Sciences, 2024)
The ritual ceremony of Naik Dango is a Dayak ethnic tradition in West Kalimantan which is still being carried out, as an expression of gratitude for having received an abundant rice harvest. Through the implementation of this ritual, researchers seek to explore the various living traditions held by the Dayak ethnic group in West Kalimantan so that they can contribute to an understanding of the traditional Dayak rituals, can explore the educative values ??contained in their implementation while at the same time preserving the ancestral traditions of the Dayak ethnic group. Using descriptive qualitative method with literary anthropology approach, data were collected by observation, recording and interviews. Data validation was carried out by means of triangulation of data sources and triangulation of methods. The implementation of the ritual ceremony of Naik Dango represents religious and creative practices as well as the customs of the Dayak ethnic group in ancient times. The educational values ??contained in the implementation of the Naik Dango ceremony are religious values, tolerance, gratitude and love for nature, social care.